Answer:
D. 4
Step-by-step explanation:
![[(p^2) (q^{-3}) ]^{-2}.[(p)^{-3}(q)^5] ^{-2}\\\\=[(p^2) (q^{-3}) \times(p)^{-3}(q)^5 ]^{-2}\\\\=[(p^{2}) \times(p)^{-3} \times (q^{-3}) \times(q)^5 ]^{-2}\\\\=[(p^{2-3}) \times (q^{5-3}) ]^{-2}\\\\=[(p^{-1}) \times (q^{2}) ]^{-2}\\\\=(p^{-1\times (-2)}) \times (q^{2\times (-2) }) \\\\=p^{2}\times q^{-4} \\\\= \frac{p^2}{q^4}\\\\= \frac{(-2)^2}{(-1)^4}\\\\= \frac{4}{1}\\\\= 4](https://tex.z-dn.net/?f=%20%5B%28p%5E2%29%20%28q%5E%7B-3%7D%29%20%5D%5E%7B-2%7D.%5B%28p%29%5E%7B-3%7D%28q%29%5E5%5D%20%5E%7B-2%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%5B%28p%5E2%29%20%28q%5E%7B-3%7D%29%20%5Ctimes%28p%29%5E%7B-3%7D%28q%29%5E5%20%5D%5E%7B-2%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%5B%28p%5E%7B2%7D%29%20%5Ctimes%28p%29%5E%7B-3%7D%20%5Ctimes%20%28q%5E%7B-3%7D%29%20%5Ctimes%28q%29%5E5%20%5D%5E%7B-2%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%5B%28p%5E%7B2-3%7D%29%20%5Ctimes%20%28q%5E%7B5-3%7D%29%20%5D%5E%7B-2%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%5B%28p%5E%7B-1%7D%29%20%5Ctimes%20%28q%5E%7B2%7D%29%20%5D%5E%7B-2%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%28p%5E%7B-1%5Ctimes%20%28-2%29%7D%29%20%5Ctimes%20%28q%5E%7B2%5Ctimes%20%28-2%29%20%7D%29%20%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3Dp%5E%7B2%7D%5Ctimes%20q%5E%7B-4%7D%20%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%20%5Cfrac%7Bp%5E2%7D%7Bq%5E4%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%20%5Cfrac%7B%28-2%29%5E2%7D%7B%28-1%29%5E4%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%20%5Cfrac%7B4%7D%7B1%7D%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%3D%204)
Answer:
0.66, 2.39
Step-by-step explanation:
two decimal places look like this. Ex: (4.74)
Answer:
y = 45/x
Step-by-step explanation:
Here, we want to write an inverse relationship
for an inverse relationship, the product of both variables will be equal to the constant term
Let us have the constant term as k
Thus, we have it that;
xy = k
9 * 5 = k
k = 45
So the inverse function is;
xy = 45
or y = 45/x
if y is a function of x, we can have it as;
f(x) = 45/x
Answer:
not enough information.
Step-by-step explanation:
W=166 degrees
okay so the total measure of the angles should be 360 so you gotta do 86+86+72+w=360
86+86+72=244
360-244=116